CoCoMac 2.0 and the future of tract-tracing databases - Bakker, Rembrandt; Wachtler, Thomas; Diesmann, Markus (Frontiers in Neuroinformatics, 2012)
The CoCoMac database contains the results of published axonal tract-tracing studies in the macaque brain. The combined data are used to construct the macaque macro-connectome. We discuss the redevelopment of CoCoMac and compare it to six connectome-related projects: two resources that provide online access to raw tracing data in rodents, a connectome viewer for advanced 3d graphics, a partial but highly detailed rat connectome, a brain data management system that generates custom connectivity matrices, and a software package that covers the complete pipeline from connectivity data to large scale brain simulations. The 2nd edition of CoCoMac features many enhancements over the original. For example, a search wizard is provided for full access to all tables. Connectivity matrices are computed on demand in a user selected nomenclature. An online data entry system is available as a preview, and is to become a generic solution for community-driven manual data entry. We end with the question whether tract-tracing will remain the gold standard to uncover the wiring of brains, thereby mentioning developments in human connectome construction, tracer substances, polarized light imaging and serial block face scanning electron microscopy.